2022
DOI: 10.1186/s13098-022-00970-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of glucagon-like peptide-1 receptor agonists with cardiac arrhythmias in patients with type 2 diabetes or obesity: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have been highly recommended for glycemic control and weight reduction. However, evidence has accumulated that GLP-1 RAs treatment is related to an increase in heart rate, which could potentially induce cardiac arrhythmias. This study aims to investigate the association of GLP-1 RAs therapy with incident arrhythmias in diabetic and obese patients. Methods MEDLINE, EMBASE, Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…GLP-1 can increase heart rate by enhancing sympathetic nervous system activation and reducing parasympathetic tone, or by direct involvement of GLP-1RA in the atrioventricular node ( 13 ). The meta-analysis by Wu S et al ( 1 ) indicated that the overall arrhythmogenic risk of this class of drugs was low, and it was linked to obesity and high-dose usage. Lorenz M et al ( 14 ) compared the extent and duration of the effects of different GLP-1RA on heart rate in healthy individuals and patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 can increase heart rate by enhancing sympathetic nervous system activation and reducing parasympathetic tone, or by direct involvement of GLP-1RA in the atrioventricular node ( 13 ). The meta-analysis by Wu S et al ( 1 ) indicated that the overall arrhythmogenic risk of this class of drugs was low, and it was linked to obesity and high-dose usage. Lorenz M et al ( 14 ) compared the extent and duration of the effects of different GLP-1RA on heart rate in healthy individuals and patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are relatively novel anti-hyperglycemic drugs that mimic the effects of endogenous GLP-1 and contribute to improved glycemic control and weight loss. Evidence has accumulated that GLP-1RAs could also be associated with improved cardiovascular outcomes and a reduction in major adverse cardiovascular events (MACEs) ( 1 ). Recent findings have shown that liraglutide significantly reduced the combined primary outcome of major adverse cardiovascular events in large cardiovascular outcome trials, elevating the importance of understanding how activation of the GLP-1R translates into clinical cardiovascular benefit ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This brings concerns about the risk of VAs and SCD in HFrEF patients. Multiple meta-analyses regarding the T2DM population did not reveal an increased risk for VAs or SCD with GLP-1 RA use [ 123 , 124 ]. The overall impact of GLP-1 RAs on VA and SCD in the HFrEF population remains inconclusive, as does their general effect in HFrEF management.…”
Section: Emerging Horizons In Heart Failure Treatmentmentioning
confidence: 99%
“…[3][4][5] However, research on the use of GLP-1RAs has shown an association of such treatment with an increase in heart rate. [6][7][8][9] Heart rate is directly inversely associated with survival in the general population and in individuals with cardiovascular conditions. 10,11 For every 5-bpm increase in heart rate in patients with coronary artery disease and left ventricular dysfunction, the risk of cardiovascular mortality and hospital admission for worsening heart failure increased by 16%.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing prevalence of T2DM, glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) have become widely used due to their clinically proven benefits in decreasing blood glucose levels and body weight 3–5 . However, research on the use of GLP‐1RAs has shown an association of such treatment with an increase in heart rate 6–9 . Heart rate is directly inversely associated with survival in the general population and in individuals with cardiovascular conditions 10,11 .…”
Section: Introductionmentioning
confidence: 99%